Adsorption Cu2+ Metal Ion Of Pectin From “Tongka Langit” Banana’s Crust (Musa Speices Van Balbisiana) - Sutapa, I Wayan; Siahay, Victor P.D.; Tanasale, Matheis F.J.D.P. (Indonesian Journal of Chemical Research, 2014)
The adsorption Cu2+ metal ion of pectin from "tongka langit" bananas crust (Musa Speices van balbisiana) has been done. Pectin was obtained from extraction "tongka langit" bananas crust with HCl at temperature 90 oC during 4 hours. Pectin was produced 9.49 grams (10.41%). Identification functional group of pectin before and after adsorption use FT-IR spectrophotometer and defractometer XRD while Cu2+ metal adsorption result was analized with using AAS. Adsorption Cu2+ metal was followed adsorption isotherm Freundlich with KF value = 4.33 mg/g and n value = 0.86.